STUDENTS’ ERROR IN CONSTRUCTING COMPLEX SENTENCES - Aulia Faradiba; Istiqlaliah Nurul Hidayati; Deddy Sofyan (Journal of English Teaching and Linguistics Studies (JET Li), 2019)
ABSTRACT The paper entitled “Students’ Error in Constructing Complex Sentences” is aimed to find out the error that students make in constructing complex sentences in interrogative form with the noun clause as dependent clause. In conducting this research, the writer applies descriptive method to describe the students’s error. The research was conducted in the fifth semester students of English Education Study Program, Faculty of Teacher Training and Educational Sciences, Pakuan University. The writer uses purposive sampling in conducting this research and takes the students who got score less than 70 in Text Based Structure.  The data were gained from three instruments: documentation, questionnaire and interview. The documentation is taken from the students’ work, questionnaires are distributed to the 60 students who become the participants and the interview is done to the lecturer who taught Text Based Structure. The writer finds out there are four types of error that students made. Those errors are omission, addition, misformation and misordering. The result shows that the highest error made by students is misformation. The writer suggests that the students should learn more about the pattern of complex sentence so they will know the verb that should be used in the noun clause as dependent clause. Keywords : students’ error, complex sentence, noun clause